2.49–4.91 GHz wideband VCO with optimised 8‐shaped inductor. Issue 1 (1st January 2019) - Zou, Wei; Zou, Xuecheng; Ren, Daming; Zhang, Kefeng; Liu, Dongsheng; Ren, Zhixiong
Abstract : A wideband low‐phase noise VCO is proposed for multi‐standard wireless communication system. An 8‐shaped high‐Q inductor is employed to enhance the performance of the VCO. The frequency pulling is reduced by using the 8‐shaped coil. Implemented in a 180 nm CMOS process, the VCO can provide a very wide tuning range of 65.4% from 2.49 to 4.91 GHz. A phase noise lower than −121.25 dBc/Hz is obtained at 1 MHz offset over the whole working band while the current consumed varies from 3.5 to 8.7 mA.